Synthetic Study on Carthamin, Part 4. Improved Synthesis of a C-Glycosyl Quinochalcone by Installation of a Side Chain through Regioselective De-O-methylation and Acyl Rearrangement - Matsuoka, Seiya; Azami, Kohei; Fujiki, Yusuke; Dohi, Reina; Yasuike, Tomokazu; Ohmori, Ken; Suzuki, Keisuke (Synlett, 2021)
We report an improved synthesis of a C-Glycosyl quinochalcone that is a key intermediate in our total synthesis of carthamin, a natural red pigment of traditional heritage. The C-glycosyl quinochalcone is prepared by regioselective de-O-methylation of a C-glycosyl bromodienone, and installation of a p-coumaroyl side chain through an O→C acyl rearrangement.
Keywords: carthamin; glycosides; chalcones; natural products; pigments